Intraductal Salivary Gland Infusion With Botulinum Toxin - Schwalje, Adam T. (Laryngoscope Investig Otolaryngol, 2019)
BACKGROUND: Administration of botulinum toxin through intraductal salivary infusion may decrease the risks of percutaneous needle injection and improve delivery to permeate the entire gland parenchyma. METHODS: The safety of intraductal salivary gland infusion was tested with prospective evaluation of two patients using interviews, clinical examination, and pressure measurement during infusion. Retrospective chart review of two subsequently treated patients assessed treatment of a parotid‐cutaneous fistula and sialorrhea. RESULTS: No complications were identified in the safety study. Pressure changes during infusion supported the concept of botulinum neurotoxin delivery to permeate the gland. Patient‐assessed success was subjectively reported as a reduction in the parotid‐cutaneous output “by 95%” and the sialorrhea “by 90%” at 2‐week follow‐up. CONCLUSIONS: The intraductal route of botulinum toxin delivery to salivary glands was without complication and was effective in two patients treated therapeutically. Pressure measurements during infusion may be helpful to direct treatment. LEVEL OF EVIDENCE: 4